The impact & importance of Sompoko program on painters of Bangladesh: a case study on Berger Paints Bangladesh - Sanjida, Faria Hossain (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.